Effect of growth conditions on glutamate transport in the wild-type strain and glutamate-utilizing mutants of Escherichia coli. - Kahane, S (1976)
The effects of growth conditions on the glutamate transport activity of intact cells and membrane vesicles and on the levels of glutamate-binding protein in wild-type Escherichia coli K-12 CS101 and in two glutamate-utilizing mutants, CS7 and CS2TC, were studied. Growth of CS101 on aspartate as the sole source of carbon or nitrogen resulted in a severalfold increase in glutamate transport activity of intact cells and membrane preparations to levels characteristic of the operator-constitutive mutant CS7. The high glutamate transport activity of mutant CS7 was not depressed further by growth on aspartate. Synthesis of glutamate-binding protein was not enhanced by aspartate in either strain. Mutant CS2TC produces a heat-labile repressor of glutamate permease synthesis and is therefore able to grow on glutamate at 42 C but not at 30 C. CS2TC cells grown in a glycerol-minimal medium at the restrictive temperature (30 C) exhibit low glutamate transport activity. Growth on aspartate at 30 C results in derepressed synthesis of glutamate permease. Cells grown on glycerol at 42 C have high glutamate transport activity. No further derepression is obtained upon growth on aspartate. Growth of CS101 and CS7 in "rich broth" greatly reduces the levels of glutamate-binding protein but does not appreciably affect glutamate transport by whole cells or membrane preparations. The identity of the carrier and the role of the binding protein in glutamate transport are discussed in the light of these findings.